Study of the influence of non-uniform thermal inclusions on the heat transfer resistance of a two-layer wall panel - Sargsyan Samvel; Agafonova Vera (BIO Web of Conferences)
The article is devoted to the analysis of the efficiency of using mineral wool slab fillers in a two-layer wall panel with different thicknesses of the external insulation layer. A literature review was conducted, which showed the relevance of the issue under consideration regarding the practical application of multilayer external enclosing structures in industrial and civil construction. A distinctive feature of such panels is their low weight, ease of transportation and installation, as well as increased energy efficiency due to the use of highly efficient fillers. The paper examines options for constructing an external wall of a residential building with different thicknesses of the external insulation layer in combination with a two-layer enclosing structure. As a result of a series of numerical calculations in the COMSOL Multiphysics software environment for various thicknesses of the external insulation of a two-layer wall panel, the nature of the temperature change across the thickness of the structure under consideration was determined. An analysis of the influence of non-uniform thermal inclusions on the equivalent heat transfer resistance of a multilayer enclosing structure was carried out. By means of engineering calculations and numerical modeling in the COMSOL Multiphysics software package, a refined value of the heat transfer resistance of a two-layer wall panel was obtained, which helps to determine the minimum thickness of the external insulation layer depending on the climatic zone of the residential building construction. It is concluded that the use of mineral wool slab fillers in the construction of multilayer wall panels increases the equivalent heat transfer resistance of the enclosing structure and also allows for a significant reduction in operating costs both at the construction stage and during the operation of buildings and structures.